Semigrupos, Automorficidade e Ergodicidade para equações de evolução semilineares - Cruz, Janisson Fernandes Dantas da (2013)
In this work, we first develop a brief theoretical approach of semigroups of bounded linear operators, culminating on Hille-Yosida Theorem. Then we used the extrapolation theory to study su cient conditions to obtain existence and uniqueness of Almost Automorphic and Pseudo-Almost Automorphic mild solutions, through the Banach's Fixed Point Theorem for the semilinear evolution equation x(t) = Ax(t) + f(t; x(t)); t E R, where A : D(A) X ! X is a Hille-Yosida operator of negative type and not necessary dense domain on the Banach space X.